If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 20)(2x + -9) = 0 Reorder the terms: (20 + 7x)(2x + -9) = 0 Reorder the terms: (20 + 7x)(-9 + 2x) = 0 Multiply (20 + 7x) * (-9 + 2x) (20(-9 + 2x) + 7x * (-9 + 2x)) = 0 ((-9 * 20 + 2x * 20) + 7x * (-9 + 2x)) = 0 ((-180 + 40x) + 7x * (-9 + 2x)) = 0 (-180 + 40x + (-9 * 7x + 2x * 7x)) = 0 (-180 + 40x + (-63x + 14x2)) = 0 Combine like terms: 40x + -63x = -23x (-180 + -23x + 14x2) = 0 Solving -180 + -23x + 14x2 = 0 Solving for variable 'x'. Factor a trinomial. (-20 + -7x)(9 + -2x) = 0Subproblem 1
Set the factor '(-20 + -7x)' equal to zero and attempt to solve: Simplifying -20 + -7x = 0 Solving -20 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -7x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -7x = 0 + 20 -7x = 0 + 20 Combine like terms: 0 + 20 = 20 -7x = 20 Divide each side by '-7'. x = -2.857142857 Simplifying x = -2.857142857Subproblem 2
Set the factor '(9 + -2x)' equal to zero and attempt to solve: Simplifying 9 + -2x = 0 Solving 9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 0 + -9 -2x = 0 + -9 Combine like terms: 0 + -9 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5Solution
x = {-2.857142857, 4.5}
| (5/14)/(3/4) | | F(7x)=7F(x) | | 4x-3=15-5x | | 0.5+2.75=17.75 | | 3(2x+1)=10x-0,6 | | 3/4(6+2x)= | | 9w=7020 | | 5/14/3/4 | | 7x+2y=-5 | | 2a+10=12 | | 4-m/8-3-m/8 | | M^2=16m | | 3x-4+=-18 | | X^5=6 | | 40x-2x=6x+12 | | 8x^2-48x+22=0 | | -9(3y-2)-4(5-6y)=0 | | 3t-12=5t+5-1 | | 7v+1=4v+7 | | -14/42-18/42w=21/42 | | 102/24 | | 10(8y-4)+5(4y-2)= | | 4.5x(2-6)= | | 6s^2=13s+28 | | 2w+6=2w+3 | | 2a-14=-3a+6 | | In(5-x)+in(-3-x)=in(1-8x) | | x^2=12.25 | | (-4+8x^2)=0 | | -5(2x-7)=15x-10 | | T+13=17 | | 2q^2+1=3q-5 |